EMPOWERING HOUSEWIFE MSMES THROUGH SUSTAINABLE HEALTHY FOOD BUSINESSES - Susan Febriantina; Inkreswari Retno Hardini; Rizki Firdausi Rachmadania; Hera Khairunnisa; Sabo Hermawan; Rayi Dwipanilih; Diva Diamantiara Dynessa; Radhit Aditya Junod (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2026)
This community service initiative, conducted on May 30, 2026, at the Aula SDIT Ummul Quro, Depok, aimed to enhance the capacity of the Sehat Bugar Baitussalam Community (KSBB) members in developing sustainable healthy food businesses.Aligned with Sustainable Development Goals (SDGs) 1 (No Poverty) and 8 (Decent Work and Economic Growth), the program equipped 31 participating housewives with essential skills through participatory training. Implemented in three systematic stages, the training covered healthy food processing based on raw food concepts and fundamental MSME accounting. Quantitative evaluation using pre-test and post-test instruments demonstrated a statistically significant improvement in participants' understanding, with average scores increasing from 85.95 to 86.87. Furthermore, 32.26% of participants exhibited marked score increases, while 41.94% maintained high stable scores. The outcomes indicate that integrating practical culinary education with foundational financial literacy is highly effective in fostering entrepreneurial independence and enabling the adoption of sustainable business models among grassroots communities.